2022
DOI: 10.3390/lubricants10050103
|View full text |Cite
|
Sign up to set email alerts
|

Data-Driven Sliding Bearing Temperature Model for Condition Monitoring in Internal Combustion Engines

Abstract: Condition monitoring of components in internal combustion engines is an essential tool for increasing engine durability and avoiding critical engine operation. If lubrication at the crankshaft main bearings is insufficient, metal-to-metal contacts become likely and thus wear can occur. Bearing temperature measurements with thermocouples serve as a reliable, fast responding, individual bearing-oriented method that is comparatively simple to apply. In combination with a corresponding reference model, such measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…Jeng and Huang [17] predicted the temperature rise of a ball bearing using a computer code that compares favourably with experimental data. In a similar trend, Laubichler [18] worked on data driven model for temperature monitoring of a sliding bearing in an internal combustion engine. Regression models like support vector, regression with Lasso boosting and without Lasso boosting were tried and the researcher concluded that the comparative studies of the models shows that the support vector regression model gave the best prediction based on the fact that it had the least root mean square error (RMSE).…”
Section: Mohammed Et Almentioning
confidence: 95%
“…Jeng and Huang [17] predicted the temperature rise of a ball bearing using a computer code that compares favourably with experimental data. In a similar trend, Laubichler [18] worked on data driven model for temperature monitoring of a sliding bearing in an internal combustion engine. Regression models like support vector, regression with Lasso boosting and without Lasso boosting were tried and the researcher concluded that the comparative studies of the models shows that the support vector regression model gave the best prediction based on the fact that it had the least root mean square error (RMSE).…”
Section: Mohammed Et Almentioning
confidence: 95%
“…On a similar approach Moosavian et al (2013) 10 compared two different methods, k-nearest neighbor and Artificial Neural Networks, to diagnose problems in ME journal bearings. Later, Laubichler et al 11 suggested a combination of data-driven bearing temperature model and thermocouple-based temperature measurements to form a powerful tool for monitoring the condition of sliding bearings in internal combustion engines. Kumar et al 12 used feed-forward neural networks to predict the minimum film thickness in plain journal bearings.…”
Section: Introductionmentioning
confidence: 99%